Environmental Factors and Protective Effects of Epigallocatechin-3-Gallate to Systemic Lupus Eritematosus: A Review Study - Herin Mawarti; Jusak Nugraha; Djoko Agus Purwanto; Joewono Soeroso (Institute of Medico-legal Publications Pvt Ltd, 2021)
SLE (Systemic Lupus Erythematosus) is one of autoimmune disease in which the immune system attacksits own tissues, causing widespread inflammation and tissue damage in the affected organs. Etiology andpathogenesis are not clearly mention until now by the scientist, but environmental factor is contribute todevelopment of Lupus and Flare disease. The objective of this study to explain the relationship betweenenvironmental factors and pathogenesis development of SLE, and how the Epigallocatechin-3-Gallate(EGCG) can protect or prevent of organs damage and environmental effects.Method: The research design of this study was used literature review. The data sources collected fromElectronic database in Pubmed, Sage, Google Scholar and website of science including reports, journals andmostly published in the last 10 years.Results: The pathomechanism of SLE was influenced by environmental factors and this was caused anincreasing of oxidative stress, chronic inflammation, dysregulation of immune system and decreased theclean of immune complex and apoptosis of cells. The production of autoantibodies and immune complex arerelated with target tissue with is it was caused chronic inflammation and the end it caused irreversible damagein glomerulus of the kidneys, arteries, lungs and other tissues. EGCG plays a protecting role in environmentalfactors as a trigger because it works as an antioxidant, anti-inflammatory and immunomudulator. So EGCGcan as a potential agent to protect SLE.Conclusion: Environmental factors plays an important role as a triger of SLE and flare. Moreover, EGCG asa potential agent to protect the presence of oxidative stress, inflammation and immune dysregulation.